2004
DOI: 10.1158/1078-0432.ccr-1157-03
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Matrix Metalloproteinase and Tissue Inhibitor Expression in Pancreatic Cancer

Abstract: Purpose: To enable the design of improved inhibitors of matrix metalloproteinases (MMPs) for the treatment of pancreatic cancer, the expression profiles of a range of MMPs and tissue inhibitors of MMPs (TIMPs) were determined.Experimental Design: Nine MMPs (MMPs 1-3, 7-9, 11, 12, and 14) and three TIMPs (TIMPs 1-3) were examined in up to 75 pancreatic ductal adenocarcinomas and 10 normal pancreata by immunohistochemistry. Eighteen additional pancreatic ductal adenocarcinomas and an additional eight normal panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
158
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(169 citation statements)
references
References 102 publications
10
158
1
Order By: Relevance
“…The critical pathologic turning point in cancer is the initiation of local invasion leading to the dissemination of tumor cells. Invasion is an active translocation of neoplastic cells across tissue boundaries through host cellular and extracellular matrix barriers (Westermarck and Kahari, 1999;Jones et al, 2004). MMP2/9, a tumor invasion signaling protein, was significantly increased in BI-1 cells (Figure 4d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical pathologic turning point in cancer is the initiation of local invasion leading to the dissemination of tumor cells. Invasion is an active translocation of neoplastic cells across tissue boundaries through host cellular and extracellular matrix barriers (Westermarck and Kahari, 1999;Jones et al, 2004). MMP2/9, a tumor invasion signaling protein, was significantly increased in BI-1 cells (Figure 4d).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, acidic media (pH 5.4-6.5) increases MMP activity in cell culture (Rofstad et al, 2006). Overall, the expression of these enzymes correlates with tumor aggressiveness (Westermarck and Kahari, 1999;Jones et al, 2004). Despite several studies of BI-1 in cancer (Grzmil et al, 2003(Grzmil et al, , 2006Harima et al, 2004), its role is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest a role for MMPs in a number of renal pathophysiologies (35 ). Many studies have shown that the overexpression of MMP-7 in several cancers is associated with advanced clinicopathological stages and unfavorable prognosis (21,36 ). Increased expression of MMP-7 has been observed in high-grade RCC tumors (24 ).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2, -7 and -9 levels in blood, pancreatic juice and tissue have been used to distinguish malignant from benign pancreatic pathologies, as well as for prognostication [83][84][85][86]. In CRC, levels of MMP-1, -7, and -13 within the malignant epithelium and stroma have been associated with decreased survival [87].…”
Section: Clinical Potential Of Extracellular Matrix Research In Digesmentioning
confidence: 99%